The Application of C4.5 Algorithm to Classify the User Satisfaction of Online Learning System - Didi Supriyadi; S. Thya Safitri (IJISTECH (International Journal of Information System and Technology), 2020)
Telkom Institute of Technology Purwokerto (ITTP) is one of the universities that always strives to improve the quality of services to stakeholders. One of the services provided is an online learning system known as e-learning. Currently, ITTP does not have an obvious measurement to determine the level of user satisfaction of the e-learning system. System user satisfaction is determined by the quality of the system. Therefore, the purpose of this research is to determine the user satisfaction of the ITTP e-learning system by referring to the attributes of the success information system model developed by DeLone & McLean. Attributes used include the Ease of use, Response time, Reliability, Flexibility, and Security. Respondent data related to the assessment of the e-learning system were further classified by applying the C4.5 Decision Tree algorithm. Based on the results of calculations and tests using Rapid Miner software, it is known that the classification of users who have the SATISFIED classification is 46 respondents and 27 respondents are DISSATISFIED. Also, it is known that the flexibility of the ITTP e-learning system is the main determinant indicator of user satisfaction followed by response time.